Efforts to prevent sexual deviation and promiscuity in adolescents - Kamariyah Kamariyah; Yuliana Yuliana; Nurlinawati Nurlinawati; Indah Mawarti (Universitas Muhammadiyah Magelang, 2023)
The goal of the community service at SMPN 21 Tanjung Jabung Timur is to educate teenagers about the physical and psychological changes, as well as the growth and use of reproductive organs that have an impact on adolescent behavior and personality during puberty. The method for providing this community service into action starts with a survey, then moves on to counseling, stimulation, and discussion using movies for young people's education. The Pre-test and Post-test are the two tests that make up this activity. The results obtained from this program are an increase in students' knowledge about changes in adolescents and the function of the reproductive work system. Apart from that, there is also an increase in students' knowledge about sexual deviation and promiscuity.